NUTRIENT UTILISATION AND GROWTH PERFORMANCE OF CLARIAS GARIEPINUS FED DIFFERENTLY PROCESSED MUCUNA UTILIS MEALS AS A REPLACEMENT FOR SOYBEAN-BASED DIET (2011)
High cost of feed and competition between fish and other livestock's feed industries necessitate research into low cost, non-conventional feedstuffs for profitable fish farming. The feed potential of Mucuna utilis in this direction has not been documented. The feed potentials of Mucuna utilis and its effects on growth and biochemical parameters of the African catfish, Clarias gariepinus were therefore investigated. Proximate, mineral composition and level of L-DOPA (3, 4-dihydroxylphenyalanine) in Raw Mucuna Meal (RMM), Cooked Mucuna Meal (CMM) and Toasted Mucuna Meal (TMM) were determined. These were used to substitute soybean meal at 0%, 10%, 20% and 30% inclusion levels in 40% crude protein isocaloric and isonitrogenous diets. Clarias gariepinus (mean weight 6.60 ± 1.09g) were randomly allotted to the 12 treatments in a 4 by 3 factorial experiment. The experiment was replicated thrice and the fish were fed twice daily at 5% body weight. The feeding trial lasted for 84 days during which growth and nutrient utilization parameters such as Mean Weight Gain (MWG), Specific Growth Rate (SGR), and Food Conversion Ratio (FCR) were measured. Packed Cell Volume (PCV), White Blood Cell (WBC), plasma glucose, plasma protein and albumin were determined. Also, histo-pathological evaluations of fish fed MSM supplemented diets were carried out. Data were analyzed using descriptive statistics and ANOVA. Crude protein (29.2%), fat (0.7%), fibre (9.6%), Potassium (1.4%), Phosphorus (0.1%) and Iron (132.1mg/kg) were highest in RMM while CMM had the least values. The level of L-DOPA was highest (6.9%) in RMM and lowest in TMM (5.2%). All the fish responded positively to experimental diets with increase in growth ranging from 12.69 ± 2.10g in 30% RMM to 18.48 ± 3.9g in 10% CMM. The MWG (20.98 ± 5.19g), SGR (11.9%), and FCR (2.81 ± 0.29) recorded in fish fed control diet (0% inclusion level) were higher but not significantly different from values obtained in fish fed diets 10% RMM and 10% TMM. Inclusion of Mucuna Seed Meal (MSM) in the diet beyond 20% in all treatments resulted in lower weight gain. Carcass protein increased in all except in fish fed 20% RMM. The PCV increased progressively from 27.0% in the control diet to 37.7% recorded in 30% inclusion level of CMM. Fish in 20% RMM had the highest WBC (8.20 X 103 ± 0.59mm3) value while the lowest value (1.01 X 103 ± 1.29mm3) was obtained in 20% inclusion level of TMM. There were no significant differences in the plasma glucose in all the treatments compared to the control value of 39.33 ± 9.24mg/l. Feeding MSM-based diets at 30% inclusion level in all the processed forms resulted in severe vacuolation of the hepatocytes of the liver and spongiosis of the white matter of the cerebellum of the brain. Mucuna seed meals have good potential as feed ingredient in the diet of Clarias gariepinus. Substitution of Mucuna seed meal as a replacement for soybean meal beyond 20% may lead to serious nutritional and health hazards to the fish.